Constricciones perturbativas al vértice quark-gluón - Fernández Rangel, Luis Albino (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
In this thesis we calculate the quark-gluon interaction vertex in perturbation theory to one loop in the asymptotic limit k2 >> p2 >> m2 of external quark momenta k and p and the bare quark mass m. This vertex consists of two Feynman diagrams of Abelian and non-Abelian nature. We calculate both these diagrams. Invoking the Slavnov- Taylor identity and subtracting out the longitudinal Ball-Chiu type vertex, we compute the transverse vertex which can help to construct a physically meaningful and reliable ansatz for its non-perturbative counterpart. Construction of this non perturbative ansatz has measurable effects in hadron physics, which are being observed in different laboratories worldwide.

En éste trabajo de tesis calculamos el vértice de interacción quark-gluón, en teoría de perturbaciones a un lazo, en el límite asintótico k2 >> p2 >> m2 de momentos externos k y p del quark y masa desnuda m del quark. Este vértice consiste de dos diagramas de Feynman de naturaleza Abeliana y no Abeliana. Ambos diagramas son calculados. Invocando las identidades de Ward-Slavnov-Taylor y restando el vértice longitudinal tipo Ball-Chiu, calculamos la parte transversa del vértice, la cual nos da pistas de cómo construir un ansatz confiable y físicamente coherente para su contraparte no perturbativa. La construcción de este ansatz no perturbativo tiene efectos medibles en física hadrónica, los cuales son observados en varios laboratorios.
Instituto de Física y Matemáticas. Maestría en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-M-2014-0248; Cromodinámica; Cuántica; Schwinger-Dyson; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1198